Toward the activation the role of banking corporate governance in reducing corruption in the Algerian banking sector - hani, meriame (Milev Journal of Research and Studies, 2016)
With the escalating of crises that experienced by many developing countries or developed recently, banks have been the common denominator in the most financial crises in those countries. Corporate governance in the banking sector is working on activating performance of banks, as well as strengthening internal oversight and follow-up of the implementation of strategies and the identification of the roles and powers of each of the shareholders and the Board of Directors and executive stakeholders further stressed the importance of transparency and disclosure. In the banking sector is becoming increasingly important to use the mechanism of honesty in financial transactions, which the searched through the study of the role of governance in reducing corruption within the Algerian banking sector, and finally this research drive us to the good application of the principles of corporate governance contributes to reduce corruption in the banking sector